Electrocardiogram events detection - Teixeira, João Paulo (2014)
This work aims to create a system of medical diagnosis of the Electrocardiogram (ECG). The events of the ECG are related with the functioning of the heart and different disorders of the heart functioning have their own ECG pattern allowing the connection between ECG patterns and cardiac disorders. For this purpose, we present here an algorithm that detects the P, QRS and T events of the ECG under MATLAB environment. The algorithm is based in two techniques. The search for picks and valleys and the search of event using a known patter and the correlation with ECG signal inside of a previously detected period. Finally the results are presented and discussed.